2018
DOI: 10.1021/acs.cgd.8b00724
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Heterogeneous Nucleation for Synthesis of Uniform Mesoporous Silica-Coated Gold Nanorods with Tailorable Rotational Diffusion and 1 nm-Scale Size Tunability

Abstract: We demonstrate a strategy for the synthesis of discrete and uniform gold nanorod (GNR)@mesoporous silica (mSiO2) core–shell nanoparticles (NPs) with finely tuned shell thickness by significantly suppressing the formation of undesired core-free NPs. We could control the thickness of the mSiO2 shell with high precision, close to 1 nm, and hence the rotational diffusion mode of NPs by simply controlling the silica precursor injection times. The growth of the mSiO2 shell on the GNR seeds and the formation of core-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 44 publications
(65 reference statements)
2
46
0
Order By: Relevance
“…Another less obvious parameter that is commonly used to modulate the thickness of the silica coating is the concentration of CTAB. Indeed, several authors observed that increasing the concentration of CTAB in solution results, for the same amount of added TEOS in thinner silica shell (Abadeer et al [ 82 ]: From 26 to 11 nm (see Figure 9 B); Yoon et al [ 83 ]: From 30 to 13 nm).…”
Section: Synthesis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another less obvious parameter that is commonly used to modulate the thickness of the silica coating is the concentration of CTAB. Indeed, several authors observed that increasing the concentration of CTAB in solution results, for the same amount of added TEOS in thinner silica shell (Abadeer et al [ 82 ]: From 26 to 11 nm (see Figure 9 B); Yoon et al [ 83 ]: From 30 to 13 nm).…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…As a consequence, the position of the l-LSPR band also allows silica shell growth monitoring. Indeed, a red shift in its position has been observed in several studies and correlated to the thickness of silica shell up to a certain value [ 83 ]. Figure 13 C illustrates the l-LSPR shift upon successive additions of TEOS resulting in silica shell thicknesses ranging from 8 to 20 nm.…”
Section: Methods Of Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…S2b †). 36,37 When 110 mL of AA was used, we found that the size of the secondary AuNPs slowly decreased, while the spherical shape was retained as the reaction progressed. Thus, by extracting samples in a timely sequence from the same batch, we were able to obtain smooth AuNPs with 1 nm-scale size tunability (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Elliptical and spherical AuNRs@mSiO 2 particles were fabricated by a slightly modied literature protocol, 19,20 and were structurally characterized by TEM and SEM. Fig.…”
Section: Resultsmentioning
confidence: 99%